Roger Scruton. In Memoriam - Roaro, Jorge (Disputatio, 2020)
Last year, Disputatio published a special edition on the topic of Humanism and its relevance in the contemporary world. One key contribution to this project would have been an interview granted by Sir Roger Scruton, one of the emminent humanists of our time. Unfortunately the illness that cut his life short at the beginning of this year made it impossible for him to answer the questions related to Humanism that we had prepared for him. This piece, In Memoriam, is a very short reflection about the importance of the philosophical legacy of Sir Roger Scruton, humanist and eclectic thinker, and a defender of a classical conception of conservatism against these times of frivolity, superficiality and unthinking egotism.